Studies on the Effect of mono-alkoxy pyrophophato coupling agent on the Mechanical Properties of Magnesium hydroxide Filled HDPE/Mg (OH)2 /TCA - 114 Composites - Alkadasi, Dr. Nabil Abdullah Noman (Journal of the Faculty of Education, 2024)
Effect of treatment of mono-alkoxy pyrophophato coupling agent on mechanical properties of composites made from High Density Polyethylene and Magnesium hydroxide is reported here. The coupling agent in the form of solution (1.5%) was used for treatment of the filler. The treatment resulted in enhancement of mechanical properties of composites when compared with composites containing untreated Magnesium hydroxide. The properties under consideration were tensile strength, modulus at (%) elongation at break, elastic modulus, hardness, etc. Although good reinforcement was observed due to treatment of 1.5% coupling agent, observed was very much remarkable to compared to untreated one. Comparison of properties of composites filled with treated and untreated Magnesium hydroxide established that treatment of Magnesium hydroxide imparts better reinforcing properties. The properties under consideration were tensile strength, (%) elongation at break, elastic modulus, hardness, etc. Tensile strength was improved by 21.43%, elastic modulus was improved by 71.53%, while hardness was improved by 1.01%, at (0.37) volume fraction.